Inverted Takotsubo-Like Left Ventricular Dysfunction with Pulmonary Oedema Developed after Caesarean Delivery Complicated by Massive Haemorrhage in a Severe Preeclamptic Parturient with a Prolonged Painful Labour - Hyejin Jeong; Seongheon Lee; Cheolwon Jeong; Jongun Lee; Seongtae Jeong; Sungsu Chung; Kyungyeon Yoo (Case Reports in Anesthesiology)
Inverted takotsubo cardiomyopathy (TTC), a variant of stress-induced cardiomyopathy, features transient myocardial dysfunction characterized by a hyperdynamic left ventricular apex and akinesia of the base. Herein, we describe a 38-year-old primigravida with severe preeclampsia who had active labour for 4 h followed by an emergency caesarean delivery. She developed postpartum haemorrhage due to uterine atony complicated by pulmonary oedema, which was managed with large-volume infusion and hysterectomy. Her haemodynamic instability was associated with cardiac biomarkers indicative of diffuse myocardial injury and echocardiographic findings of an “inverted” TTC. The patient was almost fully recovered one month later. Our case shows that a reversible inverted TTC may result from a prolonged painful labour. TTC should be listed in the differential diagnosis of the patient presenting with pulmonary oedema of unknown origin, especially in patients with severe preeclampsia.